Randomisation can do Many Things – But it Cannot "Fail". Issue 1 (25th January 2022) - Owora, Arthur H.; Dawson, John; Gadbury, Gary; Mestre, Luis M.; Pavela, Greg; Mehta, Tapan; Vorland, Colby J.; Xun, Pengcheng; Allison, David B.
Abstract: Although randomisation has long been seen as crucial to reaching reliable insights from data, it is still falling victim to some peculiar – and troublesome – misconceptions. By Arthur H. Owora, John Dawson, Gary Gadbury, Luis M. Mestre, Greg Pavela, Tapan Mehta, Colby J. Vorland, Pengcheng Xun and David B. Allison Abstract : Although randomisation has long been seen as crucial to reaching reliable insights from data, it is still falling victim to some peculiar — and troublesome — misconceptions. By Arthur H. Owora, John Dawson, Gary Gadbury, Luis M. Mestre, Greg Pavela, Tapan Mehta, Colby J. Vorland, Pengcheng Xun and David B. Allison.